The Potential of Human Umbilical Cord-Derived Mesenchymal Stem Cells as a Novel Cellular Therapy for Multiple Sclerosis - Li, Jin-Feng; Zhang, Da-Jin; Geng, Tongchao; Chen, Lin; Huang, Hongyun; Yin, Hong-Lei; Zhang, Yu-Zhen; Lou, Ji-Yu; Cao, Bingzhen; Wang, Yun-Liang (Cell transplantation, 2014)
Multiple sclerosis (MS) is a complex disease of neurological disability, affecting more than 300 out of every 1 million people in the world. The purpose of the study was to evaluate the therapeutic effects of human umbilical cord-derived mesenchymal stem cell (hUC-MSC) transplantation in MS patients. Twenty-three patients were enrolled in this study, and 13 of them were given hUC-MSC therapy at the same time as anti-inflammatory treatment, whereas the control patients received the anti-inflammatory treatment only. Treatment schedule included 1,000 mg/kg of methylprednisolone intravenously (IV) daily for 3 days and then 500 mg/kg for 2 days, followed by oral prednisone 1 mg/kg/day for 10 days. The dosage of prednisone was then reduced by 5 mg every 2 weeks until reaching a 5-mg/day maintenance dosage. Intravenous infusion of hUC-MSCs was applied three times in a 6-week period for each patient. The overall symptoms of the hUC-MSC-treated patients improved compared to patients in the control group. Both the EDSS scores and relapse occurrence were significantly lower than those of the control patients. Inflammatory cytokines were assessed, and the data demonstrated a shift from Th1 to Th2 immunity in hUC-MSC-treated patients. Our data demonstrated a high potential for hUC-MSC treatment of MS. This manuscript is published as part of the International Association of Neurorestoratology (IANR) special issue of Cell Transplantation.